Clinical case of endoscopic diagnosis of autoimmune atrophic gastritis - Ivan V. Smirnov (LLC "MEDIAFORMAT", 2022)
Autoimmune atrophic gastritis (AIG) is a chronic progressive inflammatory disease that results in damage to the gastric parietal cells and replacement of these cells by atrophic and metaplastic mucosa. In the course of the disease autoantibodies gradually destroy parietal cells, causing hypochlorhydria followed by achlorhydria; vitamin B12 absorption is also impaired. The resulting cobalamin deficiency is manifested by megaloblastic anemia and neurological disorders, the combination referred to as pernicious anemia. AIG is also associated with the increased risk of gastric adenocarcinoma and gastric neuroendocrine tumors, that is why patients diagnosed with AIG should be followed-up. Since metaplastic changes in the mucous membrane are the major histological feature found in patients with autoimmune atrophic gastritis, English sources recommend to use the term "autoimmune metaplastic atrophic gastritis". It is believed that to date AIG has been found in all populations and ethnic groups, however, there is no reliable data on the prevalence due to complexity of the diagnosis. Endoscopic diagnosis is one of the key tests for the diagnosis of AIG. The paper provides the clinical case of the endoscopic diagnosis of AIG and discusses typical endoscopic features of the disease.